MODELS OF CIRCUMSTELLAR MASERS IN BIPOLAR OUTFLOWS - Rudnitskij, G. M. (Одеські астрономічні публікації, 2017)
Sources of molecular maser radio emission in envelopes of late-type variable stars (red giants and supergiants) are considered. Radio and optical data on asymmetry of mass loss process in red giants are briefly reviewed. Main attention is paid to maser emission in the H2O rotational transition 616 — 523 (λ = 1.35 cm) of M-type supergiants (VX Sgr, VY CMa). Results of single-dish and interferometric studies of H2O maser emission of these stars are discussed. It is shown that circumstellar H2O masers in VX Sgr fit in a model of a rotating circumstellar gas-dust disc and a bipolar outflow of matter directed along the disc axis.